HUBUNGAN KADAR HEMOGLOBIN DENGAN FUNGSI KOGNITIF SISWI SMP NEGERI 6 PALANGKA RAYA - Surbakti, Ranintha Br; Sasmithae, Lia; Teresa, Astrid; Carmelita, Austin Bertilova; Millie, Gideon Christian Sonder (Jurnal Kedokteran Universitas Palangka Raya, 2023)
Teenager is a transition period from childhood to young adulthood. Teenager girls aged 13-15 years are more risky of suffering anemia than boys, because their early menstrual cycles and follow inappropriate diet patterns. Anemia can cause disruption of oxygen supply, without sufficient oxygen supply brain cells cannot develop and carry out optimal activities, which can thwart cognitive function in teenager.. Therefore, this study aims to examine the relationship between hemoglobin levels and the cognitive function of junior high school students. This cross sectional research was done at SMP Negeri 6 Palangka Raya in October 2023 with 156 subjects sample of size. It is found the average Hb level is 12.8 with 1.4 standard deviation. The lowest score of the Moca-Ina score is 13 and the highest score is 29. After conducting bivariate statistical analysis with Spearman correlation, it is found that there is an insignificant relationship between Hb levels and cognitive function. p value=0.226. This research shows that there is no statistically significant relationship between Hb levels and cognitive function.